Comparison of the intraparticle diffusion of DBT and 4, 6-DMDBT in HDS over different mesostructured silica-based catalysts. (15th September 2022) - Wang, Bo; Chen, Zhentao; Jiang, Tao; Yu, Jiahuan; Yang, Haoxuan; Duan, Aijun; Xu, Chunming
Highlights: Silica catalysts with similar activities but various pore sizes are fabricated. Hindered diffusion of DBT, 4, 6-DMDBT in various catalyst pores is studied. Pore channel/cage sizes denominate the diffusion of the reactants. Pore/molecular size > 25 can greatly reduce the intraparticle diffusion resistance. Abstract: Achieving ultradeep hydrodesulfurization (HDS) of diesel necessitates HDS catalyst optimization. Understanding the catalyst pore structure effects on the diffusion behavior of the organosulfur compound benefits the proper design of the HDS catalysts with maximized apparent reactivities. In the present study, we controllably synthesized three mesoporous silica-based catalysts (NiMo/Zr-SBA-15, FDU-12, and MCFs) with similar intrinsic reactivities (∼13 × 10 -4 and ∼ 5 × 10 -4 molg −1 h −1 for DBT and 4, 6-DMDBT HDS) but different pore structures. The diffusion behaviors of dibenzothiophene (DBT) and 4, 6-dimethyldibenzothiophene (4, 6-DMDBT) in pore channels were systematically investigated via the reaction kinetic method. The pore channel/cage sizes rather than the pore mouth/window sizes dominated the intraparticle diffusion. The effective diffusion coefficient ( D e ) decreased in the order of NiMo/Zr-MCFs (19.7 cm 2 s −1 ) > NiMo/Zr-FDU-12 (18.2 cm 2 s −1 ) > NiMo/Zr-SBA-15 (8.2 cm 2 s −1 ) for DBT, while NiMo/Zr-MCFs (7.4 cm 2 s −1 ) > NiMo/Zr-FDU-12 (4.4 cm 2 s −1 ) > NiMo/Zr-SBA-15 (4.2 cm 2 s −1 ) for 4, 6-DMDBT. The corresponding correlation with pore size suggested that the intraparticle diffusion resistance can be greatly relieved when the catalyst pore/cage size is > 25x larger than the molecule size of the organosulfur-containing compounds. The findings present fresh opportunities for designing silica-based HDS catalysts for efficient HDS reaction.